PERSEPSI DAN HARAPAN WARGA BINAAN NARKOBA TENTANG PEMBINAAN DI LEMBAGA PEMASYARAKATAN KLAS IIB PEKANBARU - Rahmad Rahmad (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2013)
Many abuses in prisons such as wrongful death, sexual perversion, bribery, which is not optimal health, torture, and the non-fulfillment of the right to a clean and healthy environment, and many more are emerging. In connection with this study it was also raised that aims to reveal the perceptions and expectations of inmates drugs on mental development, social and self-reliance in Class IIB Pekanbaru Penitentiary. This study uses a descriptive approach kantitatif. The population of inmates are drug which totaled 53 in Class IIB Pekanbaru Penitentiary, while all respondents in the sample population. Research instrument using a questionnaire with Likert scale distributed to inmates. The data was then analyzed using SPSS version 11.5. The results showed that perceptions and expectations about the development of drug inmates it can be concluded that the perception of drug inmates in prison Pekanbaru Class IIB pretty good. Meanwhile drug inmates in prisons Class IIB Pekanbaru expects coaching. This means that inmates at the prison drug class IIB Pekanbaru has given the perception that coaching is still far from their expectations related to the development of mental, social and independence.